Peningkatan Proses dan Hasil Belajar Pendidikan Pancasila Menggunakan Model Group Resume - Aulia, Salsabila Putri; Abdulah; Agrita, Tri Wera Agrita (CV. Master Literasi Indonesia, 2025)
This classroom action research was motivated by the low learning outcomes of fifth-grade students at SDN 109/II Manggis in Pancasila Education. Based on the results of the even semester exam, the average score was only 50%, still below the Minimum Passing Grade (KKM) of 70. This condition indicates the need for efforts to improve the effectiveness of learning. This study aims to analyze the effectiveness of the Group Resume learning model in improving the implementation of learning, the learning process, and student learning outcomes. The study was conducted in two cycles, each covering the stages of planning, implementation, observation, and reflection. There were 22 students participating in the study, with data collected through observation, learning motivation questionnaires, and learning outcome tests. The results showed an increase in the implementation of learning by teachers from 86% in cycle I to 90% in cycle II. The learning process of students increased from 55% (Poor category) to 91% (Very Good category), while learning outcomes increased from 73% to 91%. These findings confirm the effectiveness of the Group Resume model in improving the quality of Pancasila Education learning. The application of collaborative learning based on Group Resume can foster a sense of responsibility, cooperation, and active participation among students. This model also strengthens communication skills and critical thinking abilities through group reflection activities.